Plankton and benthos similarity indices as indicators of the impact of mangrove plantation on the environmental quality of silvofishery ponds - ENDAH DWI HASTUTI; RINI BUDI HASTUTI; SRI DARMANTI (Society for Indonesian Biodiversity, 2018)
Hastuti ED, Hastuti RB, Darmanti S. 2018. Plankton and benthos similarity indices as indicators of the impact of mangroveplantation on the environmental quality of silvofishery ponds. Biodiversitas 19: 1558-1567. This research was carried out in a coastalarea of Semarang City, Central Java, Indonesia. It aimed to study the composition of plankton and benthos communities in silvofisheryponds, and to analyze the similarity in plankton and benthos composition between ponds as an indicator of variation in pondenvironmental quality. Nine pond treatments were sampled for their plankton and benthos composition. The nine treatments consisted ofa factorial combination of three mangrove species assemblages (Avicennia marina (M1), Rhizophora mucronata (M2), and a mixture ofboth (M3)) at three mangrove populations (5 trees (S1), 10 trees (S2), and 15 trees (S3)). Similarity index analysis was conducted tomeasure the impact of treatments on the plankton and benthos communities. The total number of plankton species identified inobservation periods in May, July and September of 2016, were 23, 16 and 21 species repectively, while for the benthos there were eightsomewhat different species identified in each of the three observation periods. Fluctuation in plankton and benthos composition tendedto achieve a balance in richness by the time of the the third observation period. Diatoms, particularly Gyrosigma sp., were the mostwidely distributed plankton in the first and third observation periods, while Pyramidella sulcata was the only well-distributed benthosspecies in the three observation periods. Pairwise similarity indices between treatments ranged from 0% to 62.5% for plankton and from16.7% to 100% for benthos. The results of the investigation suggested that mangrove species affected plankton and benthos speciesrichness in this initial stage of a silvofishery development: plankton composition appeared to be richer in ponds with A. marina, whilebenthos was richer in ponds with R. mucronata.